2019
DOI: 10.3390/cells8091037
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rho GTPases by RhoGDIs in Human Cancers

Abstract: Rho GDP dissociation inhibitors (RhoGDIs) play important roles in various cellular processes, including cell migration, adhesion, and proliferation, by regulating the functions of the Rho GTPase family. Dissociation of Rho GTPases from RhoGDIs is necessary for their spatiotemporal activation and is dynamically regulated by several mechanisms, such as phosphorylation, sumoylation, and protein interaction. The expression of RhoGDIs has changed in many human cancers and become associated with the malignant phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…RhoGDIs bind to GDP-bound Rho GTPases and regulate their spatiotemporal activity. In addition, their activity is regulated by post-translational modifications (PTMs), including lipid modification, phosphorylation, ubiquitination, and sumoylation, which lead to changes in cell behavior [4].…”
Section: Introductionmentioning
confidence: 99%
“…RhoGDIs bind to GDP-bound Rho GTPases and regulate their spatiotemporal activity. In addition, their activity is regulated by post-translational modifications (PTMs), including lipid modification, phosphorylation, ubiquitination, and sumoylation, which lead to changes in cell behavior [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to current views, the expression level of small GTPases of the RhoA-family is not rate limiting for their respective activity. Rather, the activation state depends on the controlling GEFs, GAPs and GDIs in the cellular context [62]. In support of this notion it has been reported that the levels of activated Rac1 are reduced in immune cells of the Vav2 knockout mutant, while its protein levels are unchanged.…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, all three cell lines showed strong inhibition of cell migration and invasion pathways ( Figure 3 A), supporting our previous results [ 12 ]. This was most likely driven by the loss of HOTAIR and RhoGDI signalling ( Figure 3 B), with both pathways implicated in the regulation of cell migration and invasion [ 35 , 36 , 37 , 38 ]. As implicated above, the STAT3 pathway was differentially regulated across each cell line, with inhibition seen in MSTO-211H, while VMC23 and REN cells saw increasing activity trends ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%